A beam steering antenna based on Fresnel zone plate radome - Yuting Wu (Wiley, 2021)
Abstract In this study, a beam steering antenna was presented, comprising patch antenna and two layers of Fresnel zone plate (FZP). One of the FZP was a fixed structure, the other was a 1‐D collapsible radome with alternately deployed metal strips covering and non‐covering regions. The two sets of FZP were arranged in order in front of the patch antenna. First, the beam was compressed vertically by the fixed FZP. Subsequently, the beam steering was achieved with the use of the collapsible radome by setting the folding status in the respective region. To assess the effectiveness of the method, a 1‐D beam steering antenna working at 3 GHz was designed by applying linear polarized patch antenna as the feeding source. The collapsible FZP structure was developed using a low‐loss fiberglass cloth that was covered with copper strips. Based on the simulation and the experiment, the beam was focused to a beam width of 30° vertically and 10° horizontally. Moreover, 60° of beam steering in the horizontal direction could be achieved by regulating the folding angles in the respective region. This antenna design was found to be light weight and flexible, which has promising applications in 5G cell coverage and satellite communication.